2019
DOI: 10.1002/14651858.cd012245.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical tests of placental function versus ultrasound assessment of fetal size for stillbirth and small-for-gestational-age infants

Abstract: Biochemical tests of placental function versus ultrasound assessment of fetal size for stillbirth and small-for-gestational-age infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 371 publications
2
53
0
2
Order By: Relevance
“…However, it is not strongly predictive of the risk of associated complications, such as shoulder dystocia. Similar observations have been made in relation to ultrasonically suspected SGA [60,61]. That study indicated that reduced fetal abdominal growth velocity helped discriminate between healthy SGA babies and those that were at increased risk of complications.…”
Section: Plos Medicinesupporting
confidence: 75%
“…However, it is not strongly predictive of the risk of associated complications, such as shoulder dystocia. Similar observations have been made in relation to ultrasonically suspected SGA [60,61]. That study indicated that reduced fetal abdominal growth velocity helped discriminate between healthy SGA babies and those that were at increased risk of complications.…”
Section: Plos Medicinesupporting
confidence: 75%
“…Interestingly, of the SGA babies in ReMIT-2, a slightly greater proportion were delivered prior to 39 weeks' gestation in the intervention arm than in the control arm suggesting that identification of SGA babies in the intervention arm was more likely, which then prompted delivery. This observation would be consistent with the findings of the review of diagnostic test accuracy studies [17]. Nevertheless, the use of a composite outcome is a limitation of the current trial and our findings reinforce the need to ensure appropriate outcome measures are used in a main trial to enable robust conclusions to be drawn.…”
Section: Discussionsupporting
confidence: 90%
“…A recent systematic review of diagnostic test accuracy studies evaluated the ability of placental biomarkers to detect pregnancies ending in the birth of a small for gestational age (SGA) infant or a stillbirth compared with those identified via the ultrasound assessment of estimated fetal weight (EFW). This review determined that placental growth factor (PlGF) gave the highest diagnostic odds ratio (49.2; 95% confidence interval [CI] 12.7 to 191) for detecting pregnancies ending in stillbirth and performed well in the prediction of SGA neonates [17]. As the data were based on 5894 pregnancies of which only 16 ended in stillbirth and no studies investigated EFW in the prediction of stillbirth, the review concluded that further research was required to determine the diagnostic accuracy of placental biomarkers alone and in combination with EFW in the identification of adverse pregnancy outcomes [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recently the focus has shifted to non-invasive testing, such as ultrasound imaging of foetal structures and umbilical blood flow, and non-invasive prenatal screening (NIPS), designed to detect chromosome abnormalities [1]. Despite this recent focus, limited attention has pivoted to the detection of placental health as a surrogate for the well-being of pregnancy and thereby maternal and foetal health [2]. We and other investigators have recently developed novel imaging technology related to free-breathing magnetic resonance imaging including arterial spin labelling methodology that revealed detectable differences in-vivo during the early second trimester heralding subsequent development of ischaemic placental disease [3].…”
Section: Introductionmentioning
confidence: 99%